A photochemical C=C cleavage process: toward access to backbone N-formyl peptides - Wang, Haopei; Ball, Zachary T. (Beilstein Journal of Organic Chemistry, 2021)
Photo-responsive modifications and photo-uncaging concepts are useful for spatiotemporal control of peptides structure and function. While side chain photo-responsive modifications are relatively common, access to photo-responsive modifications of backbone N–H bonds is quite limited. This letter describes a new photocleavage pathway, affording N-formyl amides from vinylogous nitroaryl precursors under physiologically relevant conditions via a formal oxidative C=C cleavage. The N-formyl amide products have unique properties and reactivity, but are difficult or impossible to access by traditional synthetic approaches.
Keywords: formyl peptide; nitroaryl compound; nitroso compound; olefin cleavage; photocleavage